2017
DOI: 10.18203/2320-1770.ijrcog20170594
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of total laparoscopic hysterectomy and non-descent vaginal hysterectomy for treatment of benign diseases of uterus

Abstract: Background: Hysterectomy is the most common performed major gynaecological surgery and the decision depends on indications for operation, surgeon’s training and preference, uterine size, adnexal pathologies and patient choice. To avoid laparotomy either total laparoscopic hysterectomy (TLH) or non-descent vaginal hysterectomy (NDVH) is the recently practised option. Objectives of the present study are to compare duration of operation, blood loss, ambulation time, post-operative pain and complications between T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 5 publications
1
11
1
Order By: Relevance
“…A study by Chattopadhyay et al reported that patients who underwent TLH had significantly lower post-operative pain compared to patients undergoing NDVH, which was statistically significant. 4 Similar findings were also noted in a study by Patel et al 7…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A study by Chattopadhyay et al reported that patients who underwent TLH had significantly lower post-operative pain compared to patients undergoing NDVH, which was statistically significant. 4 Similar findings were also noted in a study by Patel et al 7…”
Section: Discussionsupporting
confidence: 87%
“…The sample size was calculated by considering the mean postoperative VAS score from the available literature. 4 VAS score in NDVH was 2.88±1.166 and TLH was 1.80±1.118. Entering these values in WinPepi software the calculated sample size obtained was 38, that is, 19 in each group.…”
Section: Methodsmentioning
confidence: 92%
“…10 Table 3 We analysed the data regarding pain in patients of both surgeries after 24 hours by VAS scoring system, we concluded that the mean pain score of patient with NDVH was 3.57+-1.3 and that of TLH was 5.4+-2.04. In contrast to the study done by chattopadhyay et al 4 in our study less pain was experienced by patient of NDVH group as compared to TLH group may be due to no incision on the abdomen as rectus sheath was neither opened nor sutured, bowel was not handled at all, peritoneal opening was minimal, gaseous distension was not required and no throat discomfort due to endotracheal intubation. Rather more pain in TLH was observed in our study which may be contributed to multiple incision on abdomen, gaseous distension, bowel handling and long operating time.…”
Section: Resultscontrasting
confidence: 96%
“…It requires less operative time, less intra operative bleeding, less post-operative morbidity, with regular infrastructural setup as observed by Shibara Chattopadhyay et al also in his study. 3,4 Even in case of scarred abdomen cervico fundal sign to feel dimpling to asses the feasibility of ndvh, as well as lateral surgical window approach makes NDVH less difficult and more safe in cases of previous abdominal surgery. 5 For uterus of 14 weeks and more debulking procidure like morcelation or coring can be done after securing uterine artery.…”
Section: Introductionmentioning
confidence: 99%
“…After a cesarean section, total laparoscopic hysterectomy (TLH) is the second most common procedure in gynecology departments [1]. Abnormal uterine bleeding (AUB), pelvic organ prolapse, leiomyoma, and cancer are routine indications for TLH [2].…”
Section: Introductionmentioning
confidence: 99%